Decision, intention, expectation, willingness, and volition: Critics and comments - Bilson Simamora (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2022)
There are thousands of studies aimed at predicting future behavior. The most outstanding concept in those quests is behavioral intention. However, many researchers fell into misusing those concepts, raising the inaccuracy of the prediction. Many researchers paid no considerable attention to the specific context of their study. This article aims to give the direction to avoid that trap and to straighten out the proper use of the concept of decision, goal intentions, specific intention, implementation, behavioral expectation, behavioral willingness, and volition. The author also outlines their relevance to a particular behavior. Original Article | Turnitin